Chronic Illness in Children : an Evidence-Based Approach - Hayman, Laura Lucia; Mahon, Margaret M.; Turner, J. Rick (Springer Pub. Co., 2002)
This book provides a research-based discussion of common childhood chronic illnesses and their etiology, diagnosis, treatment, and management. Along with information on specific diseases and conditions, such as asthma, diabetes, and arthritis, are chapters on psychosocial management, focusing on family coping, stress on the child, and adherence. This is a rich resource for nurses and other health practitioners looking for an overview of children's chronic illness in an evidence-based context.